Impact of plant parasitic nematodes & its management in Mulberry (Morus sp.) cultivation in India— A Review - Rahman, Tanvi; Rahman, Sahil; R, Kishan Kumar; S, Jashwanth (International Journal of Environment, Agriculture and Biotechnology, 2024)
Mulberry (Morus sp.), a vital crop for India's silk industry, faces significant yield reductions (10-30%) due to plant parasitic nematodes. Root-knot nematodes (Meloidogyne incognita) are primary pests, compromising plant health and leaf quality. This review provides a comprehensive analysis of nematode diversity, damage, and management strategies in Indian mulberry cultivation. The review elucidates the impact of nematode infestations on mulberry growth, yield, and quality, highlighting the need for effective management. Chemical, biological, and cultural methods are evaluated for their efficacy and sustainability. Chemical treatments, while effective, pose environmental and health risks, emphasizing the need for alternative approaches. Biological control agents, such as Trichoderma viride and Pseudomonas fluorescens, show promise in managing nematode populations. Cultural practices like crop rotation, soil solarization, and resistant cultivars are also discussed. Integrated management strategies, combining multiple approaches, are recommended for optimal results.